The role of the government in poverty alleviation in Hong Kong: Part I dynamics of policy attention, choice and change - Wong, Jennifer Shin-Chon (2017)
This discussion, as Part I of a two-part discussion, addresses Hong Kong?s poverty alleviation experience from perspectives on how problems and issues get onto policy agendas and result in various decisions and degrees of change within and beyond specific areas of policy. The alleviation initiatives taken by the government over time highlight the extent to which the processes and results have been, and remain, fluid and multi-dimensional. Significant developments are identified and assessed, as complemented by the discussion in Part II (in March 2018) of specific alleviation programmes as distinctive instruments of government policy. - Reproduced.
Keywords: Poverty alleviation - Hong Kong; Poverty alleviation